On the causes of inflation: a brief introduction to the strategic theory - Galetovic, Alexander (Estudios de Economía, 2016)
This note is a brief introduction to the strategic theory of inflation initiated by Barro and Gordon (1983a). The discussion is organized around the question of which are the causes of inflation according to the strategic theory. I show that the answer depends on whether the Central Bank can precommit itself in the very short run to choose an arbitrary rate of growth of money. If the Central Bank cannot precommit itself, it can deliberately create unexpected inflation. Then the potential short-run gains of unexpected inflation affect the long-run inflation rate –i.e these potential short-run gains are a fundamental cause of inflation not necessarily related with the long-run fiscal deficit. Moreover, the assertion that money causes inflation is not warranted.